Distribution of the Endophytic Fungi in Apple Leaves - Aminudin Afandhi; Fery Abdul Choliq; Havinda Anggrilika W.S.; Hagus Tarno (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Endophytic fungi have roles to protect the plant from herbivorous insects and diseases, and to support the absorption process of nutrients needed by plants for photosynthesis. Related to the important role of endophytic fungi, research was aimed to identify fungal endophytes associated with young, mature and old leaves on apple and to evaluate the effect of leaf ages on the abundance and diversity of endophytic fungi. The research was conducted in Biological Control Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Brawijaya from May to September 2016. Apple leaves sampling was done diagonally, and taken from nine apple trees. Based on macroscopic and microscopic characteristics, 38 isolates were identified. In the old apple leaves, it obtained 17 isolates that consisted of 5 genera, mature leaves obtained 14 isolates consisted of 6 genera, and young leaves 7 isolates obtained consists of 2 genera. The mature leaves have highest abundance and diversity of endophytic fungi compared to young and old leaves. Endophytic fungi apple leaf dominated by Aspergillus. Mature and young leaves were different from old one based on Bray-Curtis similarity.